Correlation Between the Quality of Free Body Diagram and Students' Understanding of Physics Concepts about Newton's Laws - Muhammad Nasir; Imam Wijaya; Maghfirah, Aprilla Rizki; Rusydi (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study aims to analyze the relationship between the quality of Free Body Diagram created by students and their understanding of Newton's Laws. This research employs a quantitative correlational method using a written test instrument and includes 40 eighth-grade students MTsS Lama Inong, Southwest Aceh Regency, using the purposive sampling technique. Data analysis was conducted using descriptive statistics, normality tests, linearity tests, Pearson correlation analysis, and significance tests. The results show that the average quality score of students' Free Body Diagram is 70.62, while the average conceptual understanding of physics is 60.87. The Pearson correlation test yielded a value of 0.900, with a t-value of 12.694, which is greater than the critical t-value of 2.024. The determination value of 0.804 indicates that the quality of Free Body Diagram contributes 80.4% to students' conceptual understanding. These findings demonstrate a very strong and significant relationship between the quality of Free Body Diagram created by students and their understanding of Newton's Laws. Therefore, the use of Free Body Diagram can serve as an effective instructional tool for enhancing students' conceptual. The implications of this study emphasize the importance of integrating visualization strategies in physics education to improve students' conceptual comprehension.